An Optoelectronic Equivalent Narrowband Filter for High Resolution Optical Spectrum Analysis - Kunpeng Feng (Sensors, 2017)
To achieve a narrow bandwidth optical filter with a wide swept range for new generation optical spectrum analysis (OSA) of high performance optical sensors, an optoelectronic equivalent narrowband filter (OENF) was investigated and a swept optical filter with bandwidth of several MHz and sweep range of several tens of nanometers was built using electric filters and a sweep laser as local oscillator (LO). The principle of OENF is introduced and analysis of the OENF system is presented. Two electric filters are optimized to be RBW filters for high and medium spectral resolution applications. Both simulations and experiments are conducted to verify the OENF principle and the results show that the power uncertainty is less than 1.2% and the spectral resolution can reach 6 MHz. Then, a real-time wavelength calibration system consisting of a HCN gas cell and Fabry–Pérot etalon is proposed to guarantee a wavelength accuracy of ±0.4 pm in the C-band and to reduce the influence of phase noise and nonlinear velocity of the LO sweep. Finally, OSA experiments on actual spectra of various optical sensors are conducted using the OENF system. These experimental results indicate that OENF system has an excellent capacity for the analysis of fine spectrum structures.